New 3-amino-2-thioxothiazolidin-4-one-based inhibitors of acetyl- and butyryl-cholinesterase: synthesis and activity - Krátký, Martin; Nováčková, Karolína; Svrčková, Katarína; Švarcová, Markéta; Štěpánková, Šárka (Future medicinal chemistry, 2024)
Aim: 2-Thioxothiazolidin-4-one represents a versatile scaffold in drug development. The authors used it to prepare new potent acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) inhibitors that can be utilized, e.g., to treat Alzheimer's disease. Materials & methods: 3-Amino-2-thioxothiazolidin-4-one was modified at the amino group or active methylene, using substituted benzaldehydes. The derivatives were evaluated for inhibition of AChE and BChE (Ellman's method). Results & conclusion: The derivatives were obtained with yields of 52-94%. They showed dual inhibition with IC50 values from 13.15 μM; many compounds were superior to rivastigmine. The structure-activity relationship favors nitrobenzylidene and 3,5-dihalogenosalicylidene scaffolds. AChE was inhibited noncompetitively, whereas BChE was inhibited with a mixed type of inhibition. Molecular docking provided insights into molecular interactions. Each enzyme is inhibited by a different binding mode.
Keywords: Butyrylcholinesterase; vztahy mezi strukturou a aktivitou; butyrylcholinesterasa; Acetylcholinesterase; Structure-Activity Relationship; cholinesterasové inhibitory; Cholinesterase Inhibitors; acetylcholinesterasa; Molecular Docking Simulation; simulace molekulového dockingu